In vitro antimicrobial activity of mouth washes and herbal products against dental biofilm-forming bacteria - Naiana B Da Silva; Adílis K. F. Alexandria; Aline L De Lima; Lígia V Claudino; Thiago F De Oliveira Carneiro; Adalberto C Da costa; Ana M.G. Valença; Alessandro L Cavalcanti (Wolters Kluwer Medknow Publications, 2012)
Aim: To evaluate in vitro, the antimicrobial effect of Cymbopogon citrates (lemon grass), Plectranthusamboinicus (Mexican mint) and Conyzabonariensis (hairy fleabane) tinctures as well as pure and diluted commercial mouth washes (Malvatricin® , Periogard® and Listerine® ) on wild isolates of Streptococcusmutans and reference strains of S. mutans, Streptococcus salivarius, Streptococcus oralis and Lactobacillus casei by determination of minimum inhibitory dilution (MID). Materials and Methods: 0.12% chlorhexidine and 70% corn alcohol were used as positive and negative controls, respectively. Saliva samples were collected from 3 volunteers and seeded in MSB broth to obtain Streptococcus isolates after 72-hour incubation. Using the agar diffusion method, susceptibility tests were performed with overnight incubation in microaerophilia at 37°C. All tests were performed in duplicate. Results: The bacterial species were resistant to the tinctures and Listerine® , but were susceptible to 0.12% chlorhexidine, Malvatricin® and Periogard® , with MIDs ranging from 12.5% to 1.56%. Conclusions: Plectrantusamboinicus, Conyzabonariensis and Cymbopongoncitratus tinctures and Listerine® did not show inhibitory action against the tested biofilm-forming bacteria.